Strengths and weaknesses of Bogotá as an innovation hub: Towards the governance of the regional innovation system (2013)
Bogotá is facing constraints implemented in order to strengthen its innovation capabilities and to institutionalize itself as a Regional Innovation System (RIS). Even though the city has the largest number of Higher Education Institutions (HEIs), research institutions, and technological development centres in Colombia, it is not yet positioned as an RIS. It will be necessary to do an organizational redesign in terms of the entities that comprise Bogotá and thereof its governance. The main key players of each environment were identified based on the primary role played by the different system elements. A comparative analysis was developed over time (evolution) and space (with other countries and levels of excellence) of some successful innovation cities through a methodology called Innovacities. This methodology allowed for identification of the size of the backlog confronted by the city at the frontier of technological development worldwide and the most critical factors needed to generate the breakthrough innovations to achieve world-class level. © 2013 Intellect Ltd Article. English language.